Unit and Internal Chain Profile of Millet Amylopectin. Issue 1 (13th January 2014) - Annor, George Amponsah; Marcone, Massimo; Bertoft, Eric; Seetharaman, Koushik
ABSTRACT: The unit chain compositions of debranched foxtail, proso, pearl, and finger millet amylopectins and their ϕ, β‐limit dextrins were analyzed by high‐performance anion‐exchange chromatography. The ϕ, β‐limit dextrins reflected amylopectin internal chain profiles. The amylopectins had average chain lengths ranging from 17.94 to 18.12. The ranges of external chain length, internal chain length, and total internal chain length of the millet amylopectins were 11.85–12.33, 4.75–5.09, and 11.64–12.28, respectively. The relative molar concentration of B‐chains in the amylopectins was close to 50% in all samples. Significant differences were, however, observed in the proportions of very short "fingerprint" B‐chains (Bfp, degree of polymerization 3–7) and the major group of short B‐chains (BSmajor ): foxtail and proso millets possessed high amounts of Bfp ‐chains, whereas finger and pearl millets had higher amounts of BSmajor ‐chains, suggesting possible differences in the fine structure of the clusters and building blocks of the amylopectins. Millet amylopectin can be classified structurally as type 2.